Employees’ Perceived Opportunities to Craft and In-Role Performance: The Mediating Role of Job Crafting and Work Engagement - Wingerden, Jessica van; Poell, Rob F. (Frontiers in Psychology, 2017)
The present study was designed to gain more knowledge about the influence of employees’ perceived opportunities to craft on their actual job crafting behavior and, in line with JD-R theory, subsequently their work engagement and performance. Although scholars have suggested that employees’ perceived opportunities to craft their job may predict their actual job crafting behavior, which may have consequences for their well-being and performance, no study has examined the relationships between these variables. We collected data among a heterogeneous group of Dutch employees (N=2090). Participants of the study reported their perceived opportunities to craft, job crafting behavior, work engagement and performance. Results indicated that individuals who experience a high level of opportunities to craft reported higher levels of job crafting behavior. In turn, perceived opportunities to craft and job crafting behavior related to higher levels of work engagement and subsequently performance. We discuss the implications of these findings for theory and practice.